Soft skills attributes and graduate employability: A case in Universiti Malaysia Sabah - Muhammad Ariff Nazron; Beatrice Lim Fui Yee; Janice L. H. Nga (Penerbit UMS, 2017)
This study aims to investigate the relationship between graduate’s soft skills attributes and employment status among students in Universiti Malaysia Sabah (UMS). A total of 200 respondents were surveyed using data from the feedback form on the tributes of UMS trainee who are currently undergoing industrial training in the year 2015 and the Graduate Tracer Study 2015. Using the Chi-square test, the results reveal that the attributes examined (knowledge, ICT skills, technical skills, problem solving, communication skills, team work, leadership, professionalism and ethics) have no significant relationship with the employment status of the graduates.